STRATEGI PENGEMBANGAN INDUSTRI RUMAH TANGGA GULA MERAH DI DESA BETTENG, KECAMATAN PAMBOANG, KABUPATEN MAJENE - Sudirman Sudirman; Astina Astina; Nurlaela Nurlaela; Rizka Aulia Safarni (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2026)
Betteng Village is recognized as one of the centers of traditional household-scale palm sugar production. However, the development of this industry has not yet been optimal, as it faces various complex challenges, resulting in relatively slow progress. This study aims to determine alternative strategies for the development of household palm sugar industries in Betteng Village, Pamboang District, Majene Regency. The research method employed surveys, interviews, questionnaires, and literature studies. Data were analyzed using SWOT (Strengths, Weaknesses, Opportunities, Threats) and FAHP (Fuzzy Analytical Hierarchy Process). The analysis results indicate that the value obtained from the IFE matrix is 2.543, while the value of the EFE matrix is 2.599. The household palm sugar industry in Betteng Village is positioned in cell V, which reflects an average condition both internally and externally; therefore, the appropriate strategy is hold and maintain. Based on the SWOT analysis, 13 alternative strategies were formulated. The five main priority strategies for development are: enhancing palm sugar production capacity, creating secondary packaging accompanied by attractive and informative packaging design, providing entrepreneurship training for artisans, developing product diversification of palm sugar, and expanding marketing distribution channels through both offline and online platforms.